Is being familiar with biodiversity related to reasoning about ecology?. Issue 12 (13th December 2018) - Le, Paul T.; Hartley, Laurel M.; Doherty, Jennifer H.; Harris, Cornelia B.; Moore, John C.
Abstract: Many science educators believe that student recognition of biodiversity is an important precursor to discovering patterns and understanding processes that define and shape ecological systems. We investigated (1) the total number, taxonomic categories, specificity, and diversity of backyard organisms that middle (MS) and high school (HS) students and teachers named, (2) how the number, specificity, and diversity of organisms that students and teachers named related to their overall performance on an ecology learning progression assessment, and (3) the types of information students used to sort and group organisms. Our sample population included 264 MS students, 374 HS students, and 108 teachers in five U.S. states (California, Colorado, Maryland, Michigan, and New York). We found that students were more likely to name vertebrates than plants or microorganisms, while teachers were more likely to name vertebrate and plants than microorganisms. Teachers named a higher total number (richness) and diversity of organisms and named more organisms in specific (e.g., bull snake) than general taxonomic categories (e.g., snake) than did students. Individual performance on the ecology learning progression assessment was positively correlated to the total number (richness), diversity, and specificity of organisms that students and teachers could name. The types of information students invoked to group organisms together varied by question context. Most students invoked information related to form/outward traits, habitat, function (e.g., decomposer), and taxa (e.g., fungi, plant, animal). Notably, some students invoked ideas about evolutionary relationships among organisms. This work corroborates previous findings about student familiarity with biodiversity and provides preliminary evidence that familiarity with local biodiversity is linked to reasoning about ecology.